Pemanfaatan Komposit Serat Bambu Jepang (Dracena Surculosa) dengan Penamban Material Powder - Siregar, Ansor Salim; Ineza Putri, Sunny; Maulana, Indra; Abriandika, Venusa (Fakultas Teknik UMRI, 2025)
The development of natural composites offers solutions to various material challenges, with bamboo being widely utilized as a reinforcement due to its economic value. This research investigates the influence of material mixture parameters by incorporating Japanese bamboo fibers as reinforcement, along with aluminum powder, silicon dioxide powder, fluorocarbon powder, and epoxy hardener. Bamboo fibers were extracted using a chemical method involving 5% NaOH at 70°C for varying durations. Composites were fabricated with different fiber volume fractions (26%, 32%, 38%). Impact tests on the composite materials revealed a maximum impact strength of 1.13 J/mm² with an absorbed energy of 152 Joules. The highest dd strength, 118.30 N/mm², was observed in composites with 26% fiber volume fraction. Hardness tests yielded a maximum value of 681.4 HLB for the 26% fiber variation while bending tests showed a peak result of 9.37 N/mm for the 32% fiber variation. Conversely, the water absorption test indicated the lowest absorption value of 0.56% in the 38% fiber variation.